School choice and student achievement: New evidence on open-enrolment - Martin Söderström (Institute for Labour Market Policy Evaluation (IFAU), 2006)
This paper studies the effects of open-enrolment on student performance in the context of an admission reform in Stockholm. Before 2000, students had priority to the public upper secondary school situated closest to where they lived, but from the fall of 2000 and onwards, admission is based on grades only. The reform imposed strong incentives for school competition: all students can apply to all schools, there is no targeting of students to schools, and funding follows the students. It is shown that the students in Stockholm perform no better with increased choice availability. In fact, high ability students seem to perform worse after the reform.
Keywords: I21; 330; School choice; open-enrolment; Bildungspolitik; Bildungsreform; Schule; Entscheidung; Bildungsinvestition; Bildungsertrag; Schweden